Investigation of the Hydrolytic Enzyme Activities of Candida Parapsilosis Isolated From Milk Samples of Bovine Mastitis by API ZYM and Molecular Method (Indian Journal of Forensic Medicine & Toxicology, 2020)
Two hundred and fifty milk samples were collected from cows suffering from mastitis, these samples weretested for mycotic mastitis using culture and conventional PCR method. The results showed 116 isolates ofCandida spp. were recovered with a prevalence of (46.4%),hence C. parapsilosis was the dominating species15/116 (12.9%). Fifteen isolates (100%) belong C.parapsilosis was confirmed by PCR using a speciesspecific primer for the 18S rRNA gene. Some randomly chose isolates of C. parapsilosis were used fordetection of their hydrolytic enzymatic activity by API ZYM test and PCR. The method used to evaluate theirenzymatic activity was API ZYM (BioMerieux). The highest activity was observed for leucine arylamidase,acid phosphatase, naphthol-AS-BI-phosphohydrolase and ?-glucosidase as 10/10 (100%) for each, followedby esterase lipase (C8) 9/10 (90%), valine arylamidase and alkaline phosphatase 8/10 (80%) for both andesterase (C4) 7/10 (70%). Conventional PCR was done for partial amplification of sterol esterase, alkalinephosphates and alpha-glucosidase genes by specific primer sequences, The results of the PCR amplificationof these genes was 8/10 (80%) for sterol esterase gene. Concerning the alkaline phosphatase gene, it waspresent in 10/10 (100%). Regarding alpha-glucosidase gene was present in 10/10 (100%). This work aims atevaluating enzymatic activities of C. parapsilosis isolated from cow’s milk with mastitis.